Bicentenario: 200 Jahre Unabhängigkeit in Lateinamerika Geschichte zwischen Erinnerung und Zukunft - Rinke, Stefan; Hinz, Hans-Martin; Schulze, Frederik (Historamericana, 2022)
The present conference volume with contributions by historians from Latin America, England and Germany discusses the question of independence as a point of reference for national memory in society, the public and historiography of Latin America.